IOT BASED SMART ELECTRIC METER READING, POWER THEFT AND LINE TAPPING DETECTION - Prabavathi S, Anupriyankha S, Gokulavani G, Tamilarasi K, Vishnupriya P (International Journal of Advanced Science and Technology, 2020)
Starting from the primary invented electric bulb by means of Edison to the Tesla coil, the people have travelled an extended way. The importance and utilization of electricity has become an integral part of our life.  In present day world, each little appliances proper from the electric teeth brush to huge automobiles works on energy.  Life without energy is unattainable today.  Because of advancement of technology, large quantity of electricity is generated today.  The predominant goal of the project is to broaden an IOT primarily based clever electric meter, which indicates the power units fed on and its cost for the domestic usage.  The analysing from the electric meter is transferred over the net and also despatched to the EB Web server.  The home user can also view their particular electricity usage via authentication.  Due to few technical faults like Line Tapping and Power Theft, the power losses might also occur.  The manpower couldn’t be aware of wherein the tapping occurs, by means of enforcing sensor machine the prevalence of tapping can be diagnosed and the sensor hit upon the tapping vicinity with the help of relay and ship the information to the concern individual to alert the tapping incidence.  To overcome the trouble of energy theft, a metal sensor is positioned in the electric meter box. When an electricity meter is tampered with an exposing wire the sensor detects the occurrence of energy theft and sends the information to the authorized person in order to prevent from further energy theft.